Multi objective short term hydro-thermal- CHP scheduling using social spider algorithm - Shreya Adhvaryyu; Santosh Prabhakar; Pradosh Kumar Adhvaryyu (Results in Engineering, 2022)
Potential of cheap and emission free hydro electric generation and that of another non linear efficient distributed energy resource namely combined heat and power (CHP) are utilized in the present dissertation. Water discharge from cascaded multi-reservoir system, its net head and power generation from such a hydroelectric system bears a nonlinear relationship. Such a hydro system with water transport delay among reservoirs is considered here. Optimal utilization of these sources to serve demands over short term of 24 h of a day by scheduling their respective generations so as to achieve multi objectives of cost effective production, reduced emission and transmission loss have been studied using a bio-inspired social spider algorithm. Outcome of the first test system containing hydro-thermal units shows the efficacy of the utilized optimization method while compared to other existing optimization techniques. The second test system is designed for the first time to exhibit the usefulness of the used algorithm in hydro-chp scheduling concept. Provided Statistical analysis justifies the significance of the data of the test systems.